Good Health and Well Being: Discussion from the Perspective of TCM on Post Covid-19 Symptoms - Yong, Yii Pin; Heng, Aik Teng; Wong, Ling Shing; Leong, May Ho (INTI International University, 2022)
Sustainable healthcare and well-being are major concerns in modern society. However, the healthcare support will be under great pressure, especially under critical period of time, for example the recent COVID-19 pandemic. As the pandemic is getting under control gradually, long-term consequences of COVID-19 infection are discovered, known as Long Covid syndrome, has emerged as a healthcare issue in global community. Due to the variation of symptoms, most of them are not consuming any medication but only to observe and rest. However in China, there were studies that showed Chinese medicine used to treat post COVID-19 symptoms and improve quality of life better. This article aimed to discuss the impact of Long Covid syndrome and its management from Traditional Chinese Medicine perspectives. With the success in using traditional treatments on Long Covid syndrome, more studies on traditional treatments in dealing with Long Covid-19 syndrome should be conducted to provide more holistic healthcare to the communities.